Larutan Cholerhexidine Lebih Efektif sebagai Oral Hygiene dalam Mencegah Halitosis pada Klien Penurunan Kesadaran - Firmansyah Firmansyah; Nyimas Heny Purwati; Fitrian Rayasari; Rohman Azzam; Siti Nurlaelah (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effectiveness of chlorhexidine solution on oral hygiene in preventing halitosis in clients with decreased consciousness in the ICU at PMI Hospital, Bogor. This type of research was a quiz-experimental with a research design before and after the intervention of giving chlorhexidine solution. The population and sample were 52 patients with decreased consciousness treated in the PMI Bogor Hospital ICU. Data collection techniques use observation sheets administratively. The data obtained will be analyzed univariately and bivariate with the T-test. The statistical test results showed a significant (significant) difference between the average halitosis score in the listening group and the chlorhexidine gluconate group. In conclusion, 0.12% chlorhexidine gluconate solution is more effective than a listening solution and better at preventing halitosis in patients with impaired consciousness in the ICU at PMI Hospital Bogor. Keywords: Halistosis, Chlorhexidine Solution, Oral Hygiene